Efektivitas Model Pembelajaran Kooperatif Tipe Teams Games Tournaments (TGT) untuk Meningkatkan Aktivitas dan Prestasi Belajar Siswa - Juaini, Muhammad (Mandalika Mathematics and Educations Journal, 2020)
AbstractOne of the problems of education in Indonesia is the low quality at every level and unit of education, mainly primary and secondary education. Based on observations made by researchers at SMAN 3 Selong, it was shown that the learning outcomes of Grade X MIPA-3 students obtained the lowest classical completeness, which was 37.5%, so that they had not yet achieved the classical completeness set, namely students who achieved KKM ≥ 85%. This is because teachers still use the conventional approach that is dominated by the lecture method. To overcome this, we need a learning approach that can improve student learning outcomes by connecting students' initial knowledge with the material being studied, where students are more active in the teaching and learning process. One approach that can overcome the above is the Teams Games Tournaments (TGT) cooperative learning model approach. This study aims to determine the application of the TGT type learning model in improving student learning activities and achievement on the trigonometric subject matter in class X MIPA-3 SMAN 3 Selong academic year 2019/2020 with 36 students. This type of research is Classroom Action Research consisting of planning, implementation, observation, evaluation, and reflection. The results of the study show that students are more active in the teaching and learning process, and there is an increase in mathematics learning achievement in class X MIPA-3 SMAN 3 Selong by applying a cooperative model type of TGT on trigonometric subject matter learning. This improvement in achievement can be seen from the increase in the percentage of students completeness in classical learning in the first cycle with classical completeness of 65.71%, the second cycle with classical completeness of 76.47%, and in the third cycle with classical completeness of 90.09%. Besides that, after implementing the TGT type cooperative model, student learning activities increase each cycle with active, active, and very active criteria. From the results of this study, it can be concluded that the application of the TGT type cooperative model in trigonometric subject matter learning can improve student learning activities and achievement Class X MIPA-3 SMAN 3 Selong in the academic year 2019/2020. AbstrakSalah satu permasalahan pendidikan di Indonesia adalah rendahnya mutu pada setiap jenjang dan satuan pendidikan, khususnya pendidikan dasar dan menengah. Berdasarkan hasil pengamatan yang dilakukan peneliti di SMAN 3 Selong menunjukkan bahwa hasil belajar siswa kelas X MIPA-3 memperoleh ketuntasan klasikal yang paling rendah yaitu sebesar 37,5% sehingga belum mencapai ketuntasan klasikal yang ditetapkan yaitu siswa yang mencapai KKM ≥ 85%. Hal ini disebabkan karena guru masih menggunakan pendekatan konvensional yang di dominasi metode ceramah. Untuk mengatasinya, diperlukan suatu pendekatan pembelajaran yang mampu meningkatkan hasil belajar siswa dengan menghubungkan pengetahuan awal siswa dengan materi yang sedang dipelajari, dimana siswa lebih aktif dalam proses belajar mengajar. Salah satu pendekatan yang dapat mengatasi hal tersebut di atas adalah pendekatan model pembelajaran kooperatif tipe Teams Games Tournaments (TGT).Penelitian ini bertujuan untuk mengetahui penerapan model pembelajaran tipe TGT dalam meningkatkan aktivitas dan prestasi belajar siswa pada materi pokok trigonometri di kelas X MIPA-3 SMAN 3 Selong tahun pelajaran 2019/2020 dengan jumlah siswa 36 orang. Jenis penelitian ini adalah Penelitian Tindakan Kelas yang terdiri dari perencanaan, pelaksanaan, observasi, evaluasi dan refleksi.Hasil penelitian menunjukkan bahwa siswa lebih aktif dalam proses belajar mengajar dan terjadi peningkatan prestasi belajar matematika siswa kelas X MIPA-3 SMAN 3 Selong dengan menerapkan model kooperatif tipe TGT pada pembelajaran materi pokok trigonometri. Peningkatan prestasi ini dilihat dari meningkatnya presentase ketuntasan belajar siswa secara klasikal pada siklus I dengan ketuntasan klasikal sebesar 65,71%, siklus II dengan ketuntasan klasikal sebesar 76,47% dan pada siklus III dengan ketuntasan klasikal sebesar 90,09%. Selain itu setelah mengimplementasikan dengan model kooperatif tipe TGT, aktivitas belajar siswa meningkat tiap siklusnya dengan kriteria aktif, aktif, dan sangat aktif.Dari hasil penelitian ini dapat disimpulkan bahwa penerapan model kooperatif tipe TGT pada pembelajaran materi pokok trigonometri dapat meningkatkan aktivitas dan prestasi belajar siswa kelas X MIPA-3 SMAN 3 Selong tahun pelajaran 2019 / 2020.